Review on Malaysia’s statutory minimum wage / Nurul Hayani Abd Rahman, Shaira Ismail and Nani Ilyana Shafie - Abd Rahman, Nurul Hayani; Ismail, Shaira; Shafie, Nani Ilyana (Universiti Teknologi MARA, Kedah, 2022)
In 2013, Malaysia adopted a minimum wage system. However, the wage system specifies different rates for Peninsular Malaysia, Sabah, Sarawak, and the Federal Territory of Labuan. The wage system is recommended by the National Wages Consultative Council; they suggested a set of criteria and a formula to calculate the rates. The National Wages Consultative Council was established under the National Wages Consultative Act 2011 (NWCCA 2011). The role of the Council is to obtain public opinions on the suitability of wage rate by assessing the socio-economic factors and analysing the data. The Council also formulates and recommends suitable wage rates and publishes the findings as stipulated in Section 21 of the National Wages Consultative Council Act 2011 (Ministry of Human Resource, n.d.). A simple definition of minimum wage is the lowest legal wage that organisations can offer to employees. The primary purpose of minimum wage laws is to protect workers from being exploited by employers. In addition, it aims to provide sufficient income to employees to afford a living wage, the amount needed to afford enough food, clothing, and shelter. Section 2 of the NWCCA 2011 defines minimum wage as “the basic wages to be or as determined under Section 23” (Department of Labour Peninsular Malaysia, n.d). In Section 21, the Council is required to, at such time as the Minister of Human Resources (MoHR) may determine, make a recommendation to the Government through the Minister on the following pursuant to Section 22 of the NWCCA 2011: a) the minimum wage rates; b) the coverage of the recommended minimum wage rates according to sectors, types of employment, and regional areas; c) the non-application of the recommended minimum wage rates and coverage to any sectors, types of employment, and regional areas or to any person or class of persons; d) the commencement of the minimum wage order and the different dates for the commencement of the minimum wage order to different sectors, types of employment, and regional areas, or to different persons or class of persons; and e) other matters relating to minimum wage, including the implementation of the recommended minimum wage rates and coverage. Upon recommendation, if the Government agrees with the Council in pursuant to Section 23 of the NWCCA 2011, the MOHR is required to make a minimum wage order by notification in the Federal Government Gazette. The NWCCA 2011 stated therein that the revision of the amount of minimum wage is to be revised every two years with the commencement year of 2012. 110 Since the establishment of the NWCCA in 2011, the initial minimum wage baseline in 2012 was RM900 per month for Peninsular Malaysia, RM800 per month for Sabah and Sarawak, and the Federal Territory of Labuan has raised to RM1,500 nationwide. The newly established minimum wage, which could eliminate inefficiencies in the labour market and enhance the social welfare of low-paid employees, would benefit up to one-third of the Malaysian workforce. The new rate also promotes higher labour market participation and boosts the economy's labour usage. The decision to raise the minimum wage has the potential to have far-reaching implications, even if it is unquestionably a good thing for employees in the Malaysian job market.